Effect of Vermiwash Solution on over-aged Seedlings in Root Trainer Nursery - Rao, P. S.; Murali, V.; Venkaiah, K. (Indian Forester, 2006)
An experiment conducted at Regional Forest Research Centre, Rajahmundry, Andhra Pradesh to study the effect of Vermiwash solution revealed that vermiwash can be used as "Fertigate" for maintenance of over-aged seedlings in root trainers.